PENINGKATAN PRODUKTIVITAS MY BLESSING CLOTH MELALUI TANTANGAN DAN PELUANG MANAJEMEN SUMBER DAYA MANUSIA DI ERA REVOLUSI 4.0 - Javafelistca, Renasya Caesar; Setyowati, Eni (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
The major changes occurring in the industry and economy as a result of the adoption of advanced technologies such as the internet, robotics, and artificial intelligence are challenges that need to be faced by MSMEs in the current era of the 4.0 industrial revolution, especially for those engaged in business ventures in the scope of the printing industry such as My Blessing Cloth. This era demands collaboration between humans and machines and intelligent systems to create work productivity and increase efficiency in various industrial sectors and in everyday life. So that the company's human resource management is now required to adapt new recruitment strategies to find employees who are able to manage increasingly complex technology, as well as updating employee policies to support changes in corporate culture and ways of working that are more open to innovation. The findings of this research indicate that the drive to increase My Blessing Cloth's productivity includes human resource empowerment and continuous improvement in the quality of work results so that the company is expected to be able to face and overcome all kinds of challenges and opportunities in the era of the industrial revolution 4.0.